Kreasi Sampah dan Manajemen Bank Sampah Sebagai Strategi Mewujudkan Pilar Surakarta Kota Cerdas Pangan - Purwanto, Danang; Siregar, Riadi Syafutra; Wardani, Raden Roro Ilma Kusuma; Ulfa, Amalia Nadifta; Nurhidayati, Indah; Widiyanto, Widiyanto; Santosa, Fajar Julian (Jurnal Solusi Masyarakat (JSM), 2024)
The purpose of this service is to provide knowledge, understanding, skills and proficiency to members of the Bumi Garbage Bank in waste bank management and creativity in creating waste recycling. Materials presented in the waste bank creation management and training include: (1) Waste delivery mechanism; (2) Mechanism at the waste bank; (3) types of waste with economic value; (4) Waste recycling; (5) magot cultivation. Before the activity was carried out, the participants' knowledge regarding waste bank management was limited to depositing it with the dealer or industry and experienced additional knowledge as: (1) Recycling into handicrafts such as flowerpots, wall hangings and organic fertilizers; (2) Magot cultivation which can increase economic income; (3) Facilities and infrastructure that can support the sustainability of the waste bank. Besides adding information, from this activity participants also received training on how to make plastic bottles into beautiful flowerpots and manage organic waste into fertilizer and magot feed. Based on this, it can be concluded that this service activity is able to provide valuable and cognitively positive experiences to increase the creativity of participants. Affectively growing awareness, concern for the environment and willingness to manage waste to become economically valuable.